2005
DOI: 10.1016/j.jneumeth.2005.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal development and migration in zebrafish hindbrain explants

Abstract: The zebrafish embryo is an excellent system for studying dynamic processes such as cell migration during vertebrate development. Dynamic analysis of neuronal migration in the zebrafish hindbrain has been hampered by morphogenetic movements in vivo, and by the impermeability of embryos. We have applied a recently reported technique of embryo explant culture to the analysis of neuronal development and migration in the zebrafish hindbrain. We show that hindbrain explants prepared at the somitogenesis stage underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…We favor a model in which the importance of the second cell is not in having pioneer-like capacity, but rather in being the closest FBMN to the pioneer, serving to link the pioneer to follower FBMNs. Much previous work examining FBMN migration has focused on the PCP pathway; several labs have shown that multiple components of the PCP pathway are crucial for FBMN migration both in zebrafish and in mouse Jessen et al, 2002;Carreira-Barbosa et al, 2003;Bingham et al, 2005;Wada et al, 2005;Wada et al, 2006;Rohrschneider et al, 2007;Vivancos et al, 2009;Qu et al, 2010;Walsh et al, 2011;Glasco et al, 2012). Our analysis of pioneer neurons and the MLF supports a model in which FBMN migration requires additional inputs beyond PCP signaling.…”
Section: Research Articlesupporting
confidence: 69%
See 1 more Smart Citation
“…We favor a model in which the importance of the second cell is not in having pioneer-like capacity, but rather in being the closest FBMN to the pioneer, serving to link the pioneer to follower FBMNs. Much previous work examining FBMN migration has focused on the PCP pathway; several labs have shown that multiple components of the PCP pathway are crucial for FBMN migration both in zebrafish and in mouse Jessen et al, 2002;Carreira-Barbosa et al, 2003;Bingham et al, 2005;Wada et al, 2005;Wada et al, 2006;Rohrschneider et al, 2007;Vivancos et al, 2009;Qu et al, 2010;Walsh et al, 2011;Glasco et al, 2012). Our analysis of pioneer neurons and the MLF supports a model in which FBMN migration requires additional inputs beyond PCP signaling.…”
Section: Research Articlesupporting
confidence: 69%
“…Tg(zCREST1:membRFP) embryos were placed into explant media (Bingham et al, 2005) containing L15 media (Gibco), 1 M glucose (Sigma) and pen/strep (Sigma) in a depression slide and oriented in 2% methylcellulose. The brain was severed at r2 using a set of Lumsden BioScissors (Oban Precision Instruments) at 14 hpf.…”
Section: Mlf Surgical Blockmentioning
confidence: 99%
“…4J), showing that migrating motor neurons also extend axons. A timelapse study using hindbrain explants (Bingham et al, 2005) (see Materials and methods) confirmed that the motor neurons were always located near the pial surface of the hindbrain during migration (Fig. 5A, see also Movie S1 in the supplementary material).…”
Section: Research Articlementioning
confidence: 64%
“…The procedures for time-lapse observations were essentially the same as described (Langenberg et al, 2003;Bingham et al, 2005) with modifications (H.T. and H.O., unpublished).…”
Section: Time-lapse Observationsmentioning
confidence: 99%
“…The zebrafish, Danio rerio, has been extensively used as a model for studying gene expression in developing vertebrates [19,20]. A transient high expression of HSP 70 arising in zebrafish early larvae at 80-84 h post fertilization (hpf) was repeatedly observed in our previous studies [21,22].…”
Section: Introductionmentioning
confidence: 81%